103 Indwelling peritoneal catheter insertion for malignant ascities; service evaluation and guideline production. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Armstrong, Leonie; Dewhurst, Felicity; Frew, Katie; Johnston, Robert; Robinson, Sarah; Elliot, Dawn; Aujayeb, Avinash
Abstract : Background: Conventional management of malignant ascites is recurrent inpatient paracenteses. Patients have high associated morbidity. Alternative management is insertion of an indwelling peritoneal catheter (IPC) supported by NICE, reported to have infrequent complications and associated with estimated cost saving of £1051 per patient. Our trust has an established indwelling pleural catheter service. In order to provide symptomatic benefit pleural and surgical consultants with ultrasound training started inserting IPCs in operating theatre under strict asepsis. The palliative care team is crucial to patient selection and follow up. Methods: We performed a retrospective trust-wide service evaluation followed by dissemination of results and clinical guideline production. A prospective service evaluation is ongoing. Results: From January 2016 to April 2018, 11 patients had an IPC inserted. Median age was 67. Diagnoses were pancreatic cancer (3), mesothelioma (2), breast cancer (2), colorectal cancer (1), gastric cancer (1) and oesophageal cancer (1). Mean paracenteses prior to IPC was 3.45 and mean time from initial drainage to IPC and from IPC insertion to death was 53 and 55 days respectively. 1 complication (migration of the IPC precluding drainage) arose. Following the implementation of local guidelines, 8 IPCs were inserted insertions between April and September 2018 with no complications. Median age and diagnoses were similar. However mean paracenteses prior to IPC was 1.25 and mean time from initial drainage to IPC and from IPC insertion to death was 19 and 12 days respectively. In all cases IPC insertion was associated with significant symptomatic relief. Conclusions: IPC insertion for malignant ascites is a feasible, safe and effective method of management of malignant ascites. A proactive service reduces patient's hospital visits and procedure rate significantly. Formal guidelines meant that IPCs were inserted sooner in patients who previously would have likely died with significantly symptomatic untreated ascites.